Tipe Kepribadian Ekstrover dalam Novel Seri Anak: Kajian Psikologi Sastra Carl Gustav Jung - Zhanen A’rofani Wakhid (Balai Bahasa Provinsi Riau, 2019)
This research is a study that focuses on aspects of human mentality in the form of extroverted personality types on child characters. The object of this study is a children's series novel entitled Little Ballerina and Hwaiting by Muthia Fadhilla Khairunnisa. This research is operated using a psychological study proposed by Carl Gustav Jung. The focus of this research is in the form of extroverted personality types of the main characters in the novels. Based on the focus of the study, the purpose of this research was to describe the extroverted personality type in the character of the child, namely the extroverted-minded, extroverted-feeling, extrovert-sensing, and extrovert-pioneer personality type. As a result of this research four personality types were found on the child character: on the extrovert-minded personality type, the objective minded child produced the idea; on extroverted feelings, children easily adapt; on a realistic and pleasant extrovert-sensing, child resulting from sensory stimulation; and on extrovert-pioneering personality types, fickle and creative children. This type of research is qualitative research and literary psychology as a research approach. The research data is collected using library research techniques. Data analysis was performed using descriptive analysis techniques and accompanied by in-depth interpretation.